Lung cancer among coal miners, ore miners and quarrymen: smoking-adjusted risk estimates from the synergy pooled analysis of case–control studies - Taeger, Dirk; Pesch, Beate; Kendzia, Benjamin; Behrens, Thomas; Jöckel, Karl-Heinz; Dahmann, Dirk; Siemiatycki, Jack; Kromhout, Hans; Vermeulen, Roel; Peters, Susan; Olsson, Ann; Brüske, Irene; et al. (Scandinavian Journal of Work, Environment & Health, 2015)
' ' OBJECTIVES ': 'Working in mines and quarries has been associated with an elevated lung cancer risk but with inconsistent results for coal miners. This study aimed to estimate the smoking-adjusted lung cancer risk among coal miners and compare the risk pattern with lung cancer risks among ore miners and quarrymen. ' ' METHODS ': 'We estimated lung cancer risks of coal and ore miners and quarrymen among 14 251 lung cancer cases and 17 267 controls from the SYNERGY pooled case–control study, controlling for smoking and employment in other at-risk occupations. ' ' RESULTS ': 'Ever working as miner or quarryman (690 cases, 436 controls) was associated with an elevated odds ratio (OR) of 1.55 [95% confidence interval (95% CI) 1.34–1.79] for lung cancer. Ore miners (53 cases, 24 controls) had a higher OR (2.34, 95% CI 1.36-4.03) than quarrymen (67 cases, 39 controls; OR 1.92, 95% CI 1.21–3.05) and coal miners (442 cases, 297 controls; OR 1.40, 95% CI 1.18–1.67), but CI overlapped. We did not observe trends by duration of exposure or time since last exposure. ' ' CONCLUSIONS ': 'This pooled analysis of population-based studies demonstrated an excess lung cancer risk among miners and quarrymen that remained increased after adjustment for detailed smoking history and working in other at-risk occupations. The increase in risk among coal miners were less pronounced than for ore miners or quarrymen.
Keywords: cancer; case–control study; coal miner; coal mining; histological subtype; lung cancer; mining; ore miner; ore mining; pooled analysis; population-based study; quarrymen; risk estimate; smoking